Medicinal and Aromatic Plants Network (MAPs-Net) Nepal: An open access digital database - Kunwar, RM; Thapa, KP; Shrestha, R; Shrestha, PR; Bhattarai, NK; Tiwari, NN; Shrestha, KK (Banko Janakari, 2013)
DOI: http://dx.doi.org/10.3126/banko.v21i1.9064 Banko Janakari, Vol. 21, No. 1 2011; 48-50